Facile preparation of ultralight polymer‐derived SiOCN ceramic aerogels with hierarchical pore structure. Issue 5 (16th October 2018) - Zhao, Wanyu; Shao, Gang; Han, Shixian; Cai, Chunhui; Liu, Xingcen; Sun, Mengran; Wang, Hailong; Li, Xinjian; Zhang, Rui; An, Linan
Abstract: SiOCN ceramic aerogels with lightweight, high surface areas, and macro‐meso pores have been synthesized by a facile method combining freeze‐drying technique and polymer‐derived ceramic route. The wet gels are synthesized via the hydrosilylation reaction between polysilazane and divinylbenzene with cyclohexane as solvent. The solvent is then removed by a freeze‐drying process to form pre‐ceramic aerogels. The SiOCN ceramic aerogels are finally obtained by pyrolyzing the pre‐ceramic aerogels at 1000°C in ultrahigh purity N2 . The thermogravimetric and mass spectrometry system (TG/DSC‐MS) is used to investigate the polymer‐to‐ceramic conversion process during pyrolysis. The phase composition, structure, and morphology of the SiOCN ceramic aerogels are investigated by XRD, FT‐IR, XPS, and SEM. The results show that SiOCN ceramic aerogels are composed of amorphous matrix phase and "free carbon" phase. The SiOCN aerogels possess three‐dimensional (3D) network porous structure with low density (0.19 g/cm 3 ), high specific surface area (134 m 2 /g), large pore volume (0.49 cm 3 /g), and hierarchical pore structures of both macro and meso pores. The formation mechanism and evolution process of SiOCN ceramic aerogels are discussed.